2011
DOI: 10.1118/1.3651482
|View full text |Cite
|
Sign up to set email alerts
|

Radiochromic film dosimetry of HDR 192Ir source radiation fields

Abstract: A radiochromic film based dosimetry system using only the green color channel of a flatbed document scanner showed superior precision if used alone in a dose range that extends up to 50 Gy, which greatly decreases the complexity of work. In addition, Solid Water™ material was shown to be a viable alternative to water in performing radiochromic film based dosimetry with HDR (192)Ir brachytherapy sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 37 publications
0
55
0
Order By: Relevance
“…The EBT3 estimated uncertainty is presented in the uncertainties were estimated from the literature, 32,43 assuming that EBT2 film (used by Aldelaijan et al 32 and Fonseca et al 43 ) is similar for the EBT3 model. For the response correction uncertainty, based in the estimated uncertainties of the 192 Ir film calibration fitting function, an estimated value of 0.7% was chosen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EBT3 estimated uncertainty is presented in the uncertainties were estimated from the literature, 32,43 assuming that EBT2 film (used by Aldelaijan et al 32 and Fonseca et al 43 ) is similar for the EBT3 model. For the response correction uncertainty, based in the estimated uncertainties of the 192 Ir film calibration fitting function, an estimated value of 0.7% was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…Radiochromic film has been applied extensively in external beam radiotherapy (EBRT) and brachytherapy. [29][30][31][32][33] The film used for this work was the third generation of the Gafchromic ® film, model EBT3 (Ashland, Inc., Wayne, NJ). All films used by this work were cut into (3 × 3) cm 2 pieces from the same batch (Lot No.…”
Section: B2 Radiochromic Filmsmentioning
confidence: 99%
“…These include thermoluminescent dosimeters [1720], ionisation chambers [21], semiconductor diodes [18], MOSFETS [22, 23], radiochromic film [2428] and Polymer or Fricke gel dosimetry [29]. Theoretical Monte Carlo (MC) calculations have also been extensively utilised [17, 18, 3035].…”
Section: Review Of Physics-processes In Hdr Brachytherapymentioning
confidence: 99%
“…Aldelaijan et al . [24] have shown that radiochromic film may be used in either solid water-equivalent materials or liquid water when performing radiochromic film based dosimetry with HDR brachytherapy sources, extending its usefulness. The use of polymer gel dosimetry to measure dose distribution around HDR brachytherapy sources was initially complicated due to oxygen contamination and other practical issues [44].…”
Section: Review Of Physics-processes In Hdr Brachytherapymentioning
confidence: 99%
“…The accurate results of GafChoromic TM %ilm dosimetry signi%icantly depend on the position accuracy of the source with respect to the point of interest (12) . A special attention was paid to the distances between the phantom's edge and edge of the applicator and the %ilm.…”
Section: Uncertainty Analysismentioning
confidence: 99%